Implementasi GPS (Global Positioning System) Pada Presensi Berbasis Android DI BMT Insan Mandiri - Khoir, Syaiful Amrial; Yudhana, Anton; S, Sunardi (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2020)
Attendance is a document that represents each employee at the company or representative. Some of the challenges experienced by KSPPS BMT INSAN MANDIRI are marketing that is difficult to carry out attendance when coming out of the office because of increased marketing activities that are directly related to members / out-of-office expenses. Therefore the researcher got findings to solve the problem that occurred by making an Android-based online attendance application that can be connected directly with the sarver provided by the office. This application is equipped with the introduction of security and the use of manipulations made by employees, and this application is equipped with monitoring features so that marketing managers and managers can set marketing positions in realtime. In this study, researchers used HTML and PHP programming languages for web applications that use presence servers / data centers, webside uses Google map APIs to obtain marketing positions, and presence reports can be purchased from the webside. The hope of this research is that the online android mobile attendance application with face recognition security can run well and meet the needs of the KSPPS BMT INSAN MANDIRI.